Küreselleşme Ve Yerellik Bağlamında Günümüz Türk Sineması - Ormanlı, Okan (The Turkish Online Journal of Design, Art and Communication, 2013)
The Art of Cinema, which has a past of more than a century long, is frequently discussed in terms of globalization and localization. Cinema started in Europe (France) but became a worldwide phenomenon due to the US (Hollywood). And today Hollywood, which generally represents the American cinema industry and commercial cinema, is the leader in terms of spectator and profits with billions of dollars. It constantly tries to enter every corner of the world to show / sell American movies after the rise of the globalization and sometimes makes concessions in terms of national values. Turkish cinema which is on the way to create a renaissance after the fall of Yeşilçam in terms increasing number of films and spectators by beating Hollywood’s big productions has the most percentage with its local admissions in Europe. Turkish cinema is successful at home and receives international awards almost every year but not as widespread comparing with other successful European cinemas. In this study, the reasons for the failure of Turkish, which has remained local yet also aims at taking on a more global nature, will be analyzed.
Keywords: Globalization; Cinema Industry; Turkish Cinema; Küreselleşme; Sinema Endüstrisi; Türk Sineması